Aksi Bersih Selokan sebagai Bentuk Pengabdian kepada Masyarakat dalam Mendukung Sanitasi Lingkungan - Muhammad Sahid Hudri; Agus Supriadi; I Wayan Karmana (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Environmental sanitation is an important factor in realizing a healthy and sustainable environment. One of the problems that is often encountered is the clogging of drainage channels due to the accumulation of garbage, mud, and sediment which has the potential to cause inundation, flooding, and increase the risk of environment-based diseases. This article aims to describe the implementation of community service activities through the Sewer Clean Action as an effort to support the improvement of environmental sanitation. The activity was carried out using a participatory method involving the academic community, local government, and the community through the stages of preparation, socialization, implementation of clean actions, evaluation, and documentation. The results of the activity showed an increase in the cleanliness of drainage channels, smooth water flow, high community participation, and increased public understanding and concern for the importance of maintaining environmental sanitation. In addition to having an impact on improving the physical condition of the environment, this activity also strengthens the culture of mutual cooperation and a sense of community responsibility in maintaining public facilities. Although obstacles are still found in the form of sediment accumulation and the inconsistency of some people in disposing of waste in its place, this activity has proven to be effective as a simple, easy-to-implement, and sustainable model of community service. Therefore, sewer cleaning action can be used as one of the strategies for community empowerment in supporting the creation of a clean, healthy, and sustainable environment.